Improving Students' Writing Ability Using Guided Composition - Hanafi Wibowo; Enci Zarkasih (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2020)
The phenomenon that emerge in the schools, particularly in Junior High School, just few students have a good ability in writing. Most of them have limited ability in writing. They usually take plenty of time if their teacher gives them a writing assignment. The students’ English achievement, especially in their writing ability is not sufficient. The students’ writing achievement is still low. One method that is considered to be effective to apply in language classroom is Guided Composition. It is a kind of writing composition which trains the students to write step by step. Composition might be defined as an act of putting sentences together (Spencer, 1967: 67). Constructing composition is not easy since it is a long process. Meanwhile, guided is giving the step or the way to do something.